Role of ICARDA in improving the nutritional quality and yield potential of Grasspea (Lathyrus sativus L.) for subsistence farmers in developing countries - Abd El-Moneim, Ali M.; van Dorrestein, B.; Baum, Michael; Mulugeta, W. (International Food Policy Research Institute, 1999)
Lathyrus sativus (grasspea or chickling pea) is a popular food and feed crop in certain Asia and African countries such as Bangladesh, China, Ethiopia, India, Nepal, and Pakistan, because of its resistance to drought, flood and moderate salinity and because of its need for low inputs. When other crops fail under adverse climatic conditions L. sativus can become the only available food source for the poor section of the population and sometimes is a survival food during famine. Although seeds of L. sativus are tasty and protein rich, around 30g/100g edible seeds and contain a high amount of free l-homoarginin, which can act as a precursor of lycine in higher animals. Over consumption can cause an upper neuron disease known as neurolathyrism, an irreversible paralysis of the lower limbs. The neurotoxic agents of this disease was identified as 3-N-oxalyl-L-2,3 diaminopropionic acid (ß-ODAP) or its synonym BOAA (ß-N-oxalyamino-L-alanin). The level of this compound in the dry seeds varies widely depending on genetic factors and environmental conditions. The ability of L. sativus to provide an economic yield under most adverse conditions has made it a popular crop in subsistence farming in many developing countries, and it offers a great potential for use in other parts of the world. In West Asia and North Africa (WANA) region, where under low rainfall, 250-300 mm, conditions there is tendency for increasing monoculture of cereals such as barley. The incorporation of grasspea in the rotation can make the production system more sustainable by improving soil fertility and by breaking the disease and pest cycles. The International Center for Agricultural Research in the Dry Areas (ICARDA) is placing special emphasis in improving this crop using the biodiversity available in the genetic resources. The objectives in the crop improvement program on this species are to improve its yield potential and nutritional quality through the reduction of its neurotoxin ß-ODAP content. Low neurotoxin lines having 0.07 to 0.02% ß-ODAP were developed using conventional breeding methods and by developing somaclonal variants. These lines were distributed to national program for testing under different environmental conditions. The low neurotoxin strains could have a great impact on human and livestock nutrition in those resource-poor countries with vast areas of land under semi-arid conditions.